AZD7545 is a selective inhibitor of pyruvate dehydrogenase kinase 2. (1st December 2003) - Morrell, J.A.; Orme, J.; Butlin, R.J.; Roche, T.E.; Mayers, R.M.; Kilgour, E.
Abstract : The PDH (pyruvate dehydrogenase) multi-enzyme complex catalyses a key regulatory step in oxidative glycolysis. Phosphorylation of the E1 subunit of the complex on serine residues results in the inactivation of enzyme activity. A family of four dedicated PDH kinase isoenzymes exists, each of which displays a distinct tissue-specific expression profile. AZD7545 is one of a series of PDH kinase inhibitors developed for the treatment of type 2 diabetes. The isoenzyme-selectivity profile of AZD7545 and related compounds is described and the consequences for their in vivo mode of action are discussed.